ANALISIS ISI BERITA KEKERASAN SEKSUAL TRIBUNNEWS.COM (Periode Berita Desember 2018) - Sri Hartari, I Gusti Ayu; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT This is aimed at studying the tendency of sexual violence news materials on Tribunnews.com. This research uses the normative theory method on mass media, as well as the quantitative content analysis method with descriptive approach. Data was obtained from the coding results of sexual violence news for the period of December 2018. The result of this research shows that Tribunnews.com had the tendency to publish the news of sexual violence, mainly news regarding unlawful sexual intercourse. Tribunnews.com also has the tendency to reveal victim's identity and mixing opinion and facts in writing news articles regarding sexual violence which is against the codes of ethical journalism. In the category of victim's rights, Tribunnews.com also did not follow the guidelines by having the tendency of using biased diction in writing news articles about sexual violence. Keywords: content analysis, news, sexual violence, Tribunnews.com